Influence Of Demographic Factors And History Of Malaria With The Incidence Malaria In MORU PHC - Sudirman Manumpa (Universitas Airlangga, 2017)
Malaria morbidity in Moru health center, with parameter Annual Parasite Incident (API), amounted to 16.9% in 2014. This figure was still high when compared to the target of eliminating malaria in Indonesia about <1% in 2030. Incidence of malaria is more common in children aged 5 months - <12 years. This high rates of malaria leads to poverty, low level of learning achievement of children and in pregnant women causing low birth weight in babies and death. The purpose of this study was to analyze the factors that influence the incidence of tertian and Tropikana malaria or combined Tropikana and tertian (mix) in Moru PHC in sub-district Alor Southwestern, Alor Regency.This study used a cross-sectional design, the population of study were all patients undergoing peripheral blood examination in Moru PHC's laboratory from June to October 2015. The number of samples in this study was 173 respondents. The sampling technique was Simple Random Sampling. Instruments of data collection were a questionnaire and observation sheet.Results of the study by Chi-Square test showed that the factors influencing the incidence of malaria were socioeconomic status (sig 0,000), education level (sig 0.001). By using multivariate analysis with logistic regression test, results were obtained the age of 5 months - <12 value (sig 0.025) and socioeconomic status (sig 0,000) influencing the incidence of malaria.Variables that affect the incidence of malaria were demographic factors such as age, education level, socioeconomic status. It is advisable to harness swamp thus improving the economic status of society and build permanent house. Keywords: incidence malaria, demographic factors, history of malaria